PENDIDIKAN TOLERANSI DALAM PERSPEKTIF AL-QURAN UPAYA MEMBENTUK PERILAKU HUMANIS SANTRI DI PONDOK PESANTREN - Rahmawati, Faiz; Kusmanto, Adi; Husaini, Muhammad (https://www.ejournal.smaamc.sch.id/index.php/belajar, 2024)
Tolerance education in Islamic boarding schools (pesantren) plays a strategic role in shaping students' (santri) character to appreciate diversity and differences. This study aims to explore the implementation of tolerance education in traditional (salaf) and modern pesantren, as well as the efforts of these institutions in fostering humane behavior among santri. The main focus of this research is on the application of tolerance education models in both types of pesantren, along with social and religious activities that support the development of tolerance attitudes. Research result The salaf pesantren, with its more conservative approach, teaches tolerance through the reinforcement of manners (adab), ethics (akhlak), and respect for differences. Tolerance education in salaf pesantren emphasizes the internalization of character, including respect for differences in religion, culture, and social backgrounds. On the other hand, modern pesantren adopt a more inclusive curriculum, integrating values of diversity in both academic and religious teachings. Modern pesantren emphasize understanding pluralism and multiculturalism as part of developing a more open-minded character among santri towards differences. Pesantren’s efforts to address differences are internalized through social and religious activities, which provide santri with direct experiences in interacting with a more diverse society. This study shows that both salaf and modern pesantren have complementary approaches in cultivating tolerance. These two educational models make significant contributions to the formation of humane attitudes and respect for diversity in a pluralistic society.